Main elements оf administrative leadership - Zharyk, Yevhen (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The object of research is management leadership in industrial enterprises. The purpose of the scientific article is to study the elements of effective managerial leadership and determine the most significant factors of its formation and development. Findings. A modern organization is a complex of social processes that are not always predictable. Therefore, leaders have to abandon the outdated organizational model and attempt to control people, create conditions that help workers in an environment of uncertainty to maintain an innovative focus in their actions. The urgency of the work lies in the fact that in modern conditions the Ukrainian economy is in a state of transformation and crisis. This is a serious obstacle to the effective operation of many domestic industrial enterprises, as consumer demand decreases and as a result – decreases profit from the sale of products. In this situation it is necessary to create an effective management system that will be aimed at developing effective management solutions. This is possible if there is a leader at the enterprise. The importance of managerial leadership will only grow, and, therefore, it is the leadership competencies of managers of industrial enterprises that should be reflected in the assessment of the professional and personal characteristics of managers. Research limitations/implications. To achieve the goal of the research, the following tasks were accomplished: the theoretical aspects of managerial leadership were analyzed; the models of managerial leadership are characterized depending on the degree of its effectiveness: the model of ineffective managerial leadership, the model of managerial leadership "in spite of the circumstances", the model "got out of the way", the model of effective managerial leadership; a list of key leadership competencies that a modern head of a large industrial enterprise should possess. Originality/value. The scientific significance of the work is to focus on the problems of forming and developing the leadership potential in domestic industrial enterprises and to consider possible ways of solving existing problems in their practical activities. Using the model of effective leadership will allow domestic enterprises to fully manage all areas of the enterprise in accordance with the strategic objectives of its development.